Evaluating the Planning and Implementation of the Independent Curriculum in Senior High Schools: A CIPP-Based Case Study in Semarang, Indonesia - Hartono Hartono; Hesti Pandu Wismasit; Eti Yenik; Endang Sri Darmayanti; Ngurah Ayu nyoman (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Educational planning plays a strategic role in guiding the success of policy implementation at the school level. This study aims to evaluate the planning and implementation of the Independent Curriculum in Senior High Schools in Semarang City using the CIPP evaluation model (Context, Input, Process, Product). A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The findings show that in the context aspect, schools demonstrate strong support for the new curriculum, although challenges remain in terms of understanding and infrastructure. In the input aspect, teachers were actively involved in curriculum development, yet training and technical assistance remain suboptimal. The process aspect reveals collaborative efforts among teachers, but the implementation of the Pancasila Student Profile projects and authentic assessment still face several obstacles. Meanwhile, in terms of product, teacher creativity and student participation have improved, although a comprehensive evaluation instrument for holistic learning outcomes is still lacking. These findings underscore the need to strengthen teacher training, reduce administrative burdens, and develop adaptive evaluation tools for future curriculum implementation.